2017
DOI: 10.1155/2017/9456785
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in Rats Induced by Aqueous Extract of Polygoni Multiflori Radix, Root of Polygonum multiflorum Related to the Activity Inhibition of CYP1A2 or CYP2E1

Abstract: The objective of this study is to investigate the relationship between the hepatotoxicity induced by Polygoni Multiflori Radix (PMR, root of Polygonum multiflorum Thunb., He Shou Wu) and the activity of CYP1A2 or CYP2E1 in the rat liver. Levels of rat serum transaminases ALT and AST were not altered but the activity of CYP1A2 or CYP2E1 in the rat liver was significantly inhibited after oral administration of aqueous extract of PMR under the experimental dosage. However, levels of ALT and AST were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Unfortunately, no satisfactory biomarkers are currently available to identify human populations susceptible to this injury. Moreover, conventional animal models in which only high doses that significantly exceed the typical PM dose that can induce liver injury are not suitable for mimicking dose‐independent, PM‐induced idiosyncratic hepatotoxicity. Recently, however, a rat model of immune action–mediated liver injury induced by cotreatment with a nontoxic dose of lipopolysaccharide and a therapeutic dose of PM exhibited liver injury characteristics similar to those shown in humans and induced a state of immune activation and inflammatory stress .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no satisfactory biomarkers are currently available to identify human populations susceptible to this injury. Moreover, conventional animal models in which only high doses that significantly exceed the typical PM dose that can induce liver injury are not suitable for mimicking dose‐independent, PM‐induced idiosyncratic hepatotoxicity. Recently, however, a rat model of immune action–mediated liver injury induced by cotreatment with a nontoxic dose of lipopolysaccharide and a therapeutic dose of PM exhibited liver injury characteristics similar to those shown in humans and induced a state of immune activation and inflammatory stress .…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al indicated that the frequency of the cytochrome P450 (CYP) 1A2 1C mutation in Chinese patients with PM-induced acute liver injury was higher than in healthy controls [ 31 ]. In addition, the aqueous PM extract induced hepatotoxicity in rats only in combination with the inhibition of CYP1A2 and CYP2E1 activities [ 32 ]. This implies that CYP enzymes mediate PM metabolism; however, individuals with these pathogenic single-nucleotide polymorphisms may also have increased susceptibility to drug-induced liver injury, which may be less directly related to the potential toxicity of PM.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the application of modern preparation technology increases the yield of active ingredients and also increases the yield of toxic components, which may lead to adverse reactions (Zhang et al, 2015). In some studies, Lu et al compared the differences in hepatotoxicities of different PM extraction solvents, and found that 50% ethanol extract was the most toxic Deng-Ke et al, 2017). In addition, Liang et al compared the differences in hepatotoxicities of ethanol extracts and water extracts, and reported that the toxicity of alcohol extracts was much higher than those of water extracts and medicinal materials, suggesting that hepatotoxic substances of PM may be concentrated in the alcohol extract (Liang et al, 2010).…”
Section: Improper Modern Preparation Process Modern Extraction Procesmentioning
confidence: 99%